2023
DOI: 10.1111/febs.16812
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein‐3: 63Cu(I) binds to human 68Zn7‐βα MT3 with no preference for Cu4‐β cluster formation

Abstract: Human metallothioneins (MTs) are involved in binding the essential elements, Cu(I) and Zn(II), and the toxic element, Cd(II), in metal‐thiolate clusters using 20 reduced cysteines. The brain‐specific MT3 binds a mixture of Cu(I) and Zn(II) in vivo. Its metallation properties are critically important because of potential connections between Cu, Zn and neurodegenerative diseases. We report that the use of isotopically pure 63Cu(I) and 68Zn(II) greatly enhances the element resolution in the ESI‐mass spectral data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
1
1
0
Order By: Relevance
“…Their findings revealed the existence of several species including αCu 4 MT2, βCu 6 MT2, and βCu 6 αCu 4 MT2. These results are in line with those from the Stillman group, who studied Cu­(I) binding to apoMT1a and showed that the α-domain binds four Cu­(I) ions, while the β-domain binds six Cu­(I), forming copper-thiolate clusters. , In their recent research, they showed that Cu­(I) (not Cu­(II)) binds to Zn 7 MT3 forming multiple species, with no preference for Cu 4 Zn 4 MT3 . In another study, Melenbacher et al studied Cu­(I) binding to Zn 7 MT1a instead of apoMT1a .…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Their findings revealed the existence of several species including αCu 4 MT2, βCu 6 MT2, and βCu 6 αCu 4 MT2. These results are in line with those from the Stillman group, who studied Cu­(I) binding to apoMT1a and showed that the α-domain binds four Cu­(I) ions, while the β-domain binds six Cu­(I), forming copper-thiolate clusters. , In their recent research, they showed that Cu­(I) (not Cu­(II)) binds to Zn 7 MT3 forming multiple species, with no preference for Cu 4 Zn 4 MT3 . In another study, Melenbacher et al studied Cu­(I) binding to Zn 7 MT1a instead of apoMT1a .…”
supporting
confidence: 83%
“… 36 , 37 In their recent research, they showed that Cu(I) (not Cu(II)) binds to Zn 7 MT3 forming multiple species, with no preference for Cu 4 Zn 4 MT3. 38 In another study, Melenbacher et al studied Cu(I) binding to Zn 7 MT1a instead of apoMT1a. 39 Their results suggested the formation of two main complexes, βZn 1 Cu 5 αZn 4 MT1a and βCu 6 αZn 4 MT1a.…”
mentioning
confidence: 99%
“…When using Cu(I) as a metal source rather than Cu(II), no domain preference was observed. 47,48 Therefore, these results indicate that the intramolecular disulfide formation formed upon Cu(II) reduction to Cu(I) dictates the domain preference and not the nature of the metal ion.…”
Section: Cid Experiments On Cu(i)/zn(ii)-nem X Mt3 Ox Speciesmentioning
confidence: 90%
“…43−46 Interestingly, no preference for a specific domain was found when using Cu(I) titrations on Zn 7 MT3. 47,48 Using this protein, we demonstrated that NEM could be employed in the initial labeling step to dissociate all Zn(II) ions while Cu(I) remains bound due to its higher affinity for Cys. In the second labeling step, an excess of IAM is utilized to label Cu(I)-bound Cys residues, leading to Cu(I) dissociation.…”
Section: ■ Introductionmentioning
confidence: 99%